2017
DOI: 10.3389/fphys.2017.00446
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Exposure to Lead Induces Cognitive Impairment in Elder Mice Targeting SIRT1 Phosphorylation and Oxidative Alterations

Abstract: Pb is a potential risk factor for cognition, mainly mediated by enhanced oxidative stress. Resveratrol, a natural polyphenol with crucial anti-oxidative property, is recently implicated in preventing cognitive deficits in normal aging and neurodegenerative disorders. Its beneficial effects have been linked to sirtuin 1(SIRT1) activation. The aim of this work is to investigate the possible linkage between alterations in Pb-induced oxidative damage and cognitive impairment by prolonged treatment of resveratrol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 49 publications
6
27
0
Order By: Relevance
“…The most significant and important finding in our study was the discovery of memory loss in adult zebrafish induced by chronic PbCl 2 exposure at a concentration of 50 ppb. This finding is consistent with previous publications about the neurotoxicity and memory impairment induced by chronic lead exposure in rodents [28][29][30]. On the other hand, the study done by Chen et al also showed that the 25 to 50 ppb lead acetate exposure of 8 to 120 hpf zebrafish induced memory deficiency at the adult stage (determined at 150 dpf), which was tested by food reward-based T-maze [6].…”
Section: Discussionsupporting
confidence: 91%
“…The most significant and important finding in our study was the discovery of memory loss in adult zebrafish induced by chronic PbCl 2 exposure at a concentration of 50 ppb. This finding is consistent with previous publications about the neurotoxicity and memory impairment induced by chronic lead exposure in rodents [28][29][30]. On the other hand, the study done by Chen et al also showed that the 25 to 50 ppb lead acetate exposure of 8 to 120 hpf zebrafish induced memory deficiency at the adult stage (determined at 150 dpf), which was tested by food reward-based T-maze [6].…”
Section: Discussionsupporting
confidence: 91%
“…This result indicates that Pb treatment may have affected the ability of the animals to learn or remember the location of the dark box earlier than expected after several trial period. This finding supported several earlier reports that implicated Pb EAHT exposure as an agent of cognitive impairment, particularly in a developing brain [13,[33][34][35]. This result further indicates that the treatment of Vitexin alongside Pb treatment will attenuate the possible cognitive impairment caused by Pb.…”
Section: Discussionsupporting
confidence: 91%
“…Exposure to Pb, even in low doses, results in various adverse consequences, particularly in the brain [8]. Pb, as a neurotoxicant, crosses the blood-brain barrier to cause oxidative stress [9], morphologic damage, neurodegeneration and cognitive impairment in the brain, particularly that of developing brain [10][11][12][13]. The prefrontal cortex (PFC), which accounts for one-third of the human cerebral cortex, is responsible for working memory, higher reasoning, decision making and many other executive functions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…lead is a heavy metal widely used in various industries, its release can permanently pollute the environment [1] .It has been well documented that lead exposure can develop multiple systemic adverse effects, including decreased intelligence quotient (IQ) [2,3] cognitive impairment [4][5][6] memory decline [7,8] and de cient attention [9][10][11] as well as known hematological toxicities.. In addition, recent studies have reported that lead exposure may aggravate neurodegenerative disorders, such as Alzheimer's and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%